Natural-cycle in vitro fertilization (IVF) combined with in vitro maturation in infertile patients with polycystic ovarian syndrome (PCOS) requiring IVF - Claudia González-Ortega; Raul E. Piña-Aguilar; Patricia Cancino-Villarreal; Efraín Pérez-Peña; Antonio M. Gutiérrez-Gutiérrez (Elsevier, 2019)
Objective: In this study, we report an experience of 59 natural-cycle IVF combined with in vitro oocyte maturation (IVF/M) cycles in patients with PCOS requiring IVF recruited based on limitations to afford a conventional IVF treatment in a 9-years period. Results of IVF/M were compared with 164 cycles of IVF in PCOS patients. Material and methods: In IVF/M cycles only hCG priming was used before oocyte recovery, with in vitro maturation of immature oocytes in a commercial medium. In conventional IVF group, recombinant FSH (rFSH) and GnRH agonist/antagonist for ovarian stimulation were used. In both groups, fertilization was achieved by intracytoplasmic sperm injection (ICSI) of mature oocytes and fresh embryos transferred at day 2 or day 3. Results: In all IVF/M cycles oocytes and transferable quality embryos were obtained, only in 6 IVF/M cycles mature oocytes were obtained at oocyte capture day. Clinical pregnancy rate per cycle was 39.0% vs 53.6% (p = 0.0682) and delivery rate per cycle was 30.5% vs 42.6% (p = 0.1209) in IVF/M and conventional IVF respectively. Patients with ovarian hyperstimulation syndrome (OHSS) were 0% in IVF/M vs 6.7% in conventional IVF (p = 0.0399). Conclusion: Our experience in a private clinic in Mexico suggests that IVF/M can be a useful initial strategy to treat PCOS patients requiring IVF with comparable delivery rates to conventional IVF and a decreased risk of ovary hyperstimulation. IVF/M may be indicated to patients with limited resources paying without insurance for their infertility treatment. Keywords: In vitro maturation, PCOS, Infertility, Mild approach, Patient friendly IVF